2017
DOI: 10.1111/bph.13779
|View full text |Cite
|
Sign up to set email alerts
|

Principles of pharmacological research of nutraceuticals

Abstract: Linked Articles This article is part of a themed section on Principles of Pharmacological Research of Nutraceuticals. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v174.11/issuetoc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
117
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(118 citation statements)
references
References 155 publications
0
117
0
1
Order By: Relevance
“…Coumarins are known for their anticoagulant effects. The observation of fatal hemorrhage in cattle eating mouldy sweet clover, as a result of impaired coagulation, led to the introduction in therapy of the anticoagulant drug dicoumarol, which is chemically related to warfarin (Andrew & Izzo, ). A Norwegian study has recently shown that children eating oatmeal porridge several times a week sprinkled with cinnamon could have a coumarin intake greatly exceeding the tolerable daily intake (Fotland, Paulsen, Sanner, Alexander, & Husøy, ).…”
Section: Phenolic Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Coumarins are known for their anticoagulant effects. The observation of fatal hemorrhage in cattle eating mouldy sweet clover, as a result of impaired coagulation, led to the introduction in therapy of the anticoagulant drug dicoumarol, which is chemically related to warfarin (Andrew & Izzo, ). A Norwegian study has recently shown that children eating oatmeal porridge several times a week sprinkled with cinnamon could have a coumarin intake greatly exceeding the tolerable daily intake (Fotland, Paulsen, Sanner, Alexander, & Husøy, ).…”
Section: Phenolic Compoundsmentioning
confidence: 99%
“…Within nutraceuticals (Andrew & Izzo, ; Daliu, Santini, & Novellino, ; Durazzo & Lucarini, ; Santini et al, ; Santini & Novellino, ; Santini & Novellino, ; Santini, Tenore, & Novellino, ), more than 8,000 different phenolics are identified in the plant kingdom and represent one of most numerous and widely distributed class of plant secondary metabolites (Cheynier, Comte, Davies, Lattanzio, & Martens, ; Kabera, Semana, Mussa, & He, ; Santini, Novellino, Armini, & Ritieni, ). Several outstanding reviews on polyphenols have been recently published (Amiot, Riva, & Vinet, ; Bernatoniene & Kopustinskiene, ; Białecka‐Florjańczyk, Fabiszewska, & Zieniuk, ; Clifford, Jaganath, Ludwig, & Crozier, ; Costa et al, ; Durazzo et al, ; Pervaiz, Songtao, Faghihi, Haider, & Fang, ; Roche et al, ; Xiao, Zhang, Tong, & Shi, ; H. Zhang & Tsao, ; Zhao et al, ), and the reader is referred to them for a more in‐depth information.…”
Section: Introductionmentioning
confidence: 99%
“…The requirement of a strict quality control program (physical–chemical and microbiological analyses) has to include the whole manufacturing process from the cultivation, plant collection, drying and storage, extract preparation, to the production, and packaging of the final product. In addition, herbal preparations may present with both pharmacokinetic and pharmacodynamics interactions if taken in conjunction with other over‐the‐counter or prescription drugs (Andrew & Izzo, ; Cordell & Colvard, ; Gohil & Patel, ; Izzo et al, ; Mohamed et al, ; J. Zhang et al, ). Some of these interactions are not well studied to date and hence make healthcare providers reluctant to recommend dietary supplements in general.…”
Section: Specific Considerations For the Use Of Herbal Medicines Durimentioning
confidence: 99%
“…Women often use herbal dietary supplements and herbal medicines during pregnancy, typically based on the belief that the use of such products is safe (Eisenberg et al, ; Fakeye, Adisa, & Musa, ; Hall, Griffiths, & McKenna, ; Hall, Griffiths, & McKenna, ; Kennedy, Lupattelli, Koren, & Nordeng, ; World Health Organization [WHO], ). Herbal medicines have been defined by the World Health as “any medicinal product based on herbs, herbal materials, herbal preparations and finished herbal products that contain as active ingredients parts of plants, other plant materials, or combinations thereof” (Andrew & Izzo, ; WHO, ). According to a study done in Nigeria (Fakeye et al, ), where the use of herbal medicines in women's health is very common, the reasons and beliefs are diverse, but among them are the following: medicinal plants have better efficacy than pharmaceutical drugs (22.4%); herbal medicines are natural and therefore viewed as safer than conventional drugs during pregnancy (21.1%); low effectiveness of conventional medicines (19.7%); the easy access to herbal medicines (11.2%); the traditional and cultural belief that herbal medicines can heal many diseases (12.5%); and comparatively, the low cost of herbal medicines (5.9%).…”
Section: Introductionmentioning
confidence: 99%
“…The rising rates of obesity in the world, the limited success of lifestyle changes, and pharmacotherapy—associated to the lack of compliance of the pharmacological treatment—drive many people towards the use of products invariably defined as nutraceuticals, dietary supplements, or herbal medicinal products (Andrew & Izzo, ; Farrington, Musgrave, & Byard, ; Ríos‐Hoyo & Gutiérrez‐Salmeán, ). The popularity of such treatments for weight management has increased in the last years, and a wide variety of these products are available over the counter (Ríos‐Hoyo & Gutiérrez‐Salmeán, ).…”
mentioning
confidence: 99%